Precipitation Method for Barium Metaborate (BaB2O4) Synthesis from Borax Solution - Aksener, Eymen; Kanturk Figen, Aysel; Piskin, Sabriye (AMER INST PHYSICS, 2013)
In this study, barium metaborate (BaB2O4, BMB) synthesis from the borax solution was carried out. BMB currently is used in production of ceramic glazes, luminophors, oxide cathodes as well as additives to pigments for aqueous emulsion paints and also beta-BaB2O4 single crystals are the best candidate for fabrication of solid-state UV lasers operating at a wavelength of 200 nm due to excellent nonlinear optical properties. In the present study, synthesis was carried out from the borax solution (Na2B4O7 center dot 10H(2)O, BDH) and barium chloride (BaCI2 center dot 2H(2)O, Ba) in the glass-batch reactor with stirring. The effect of, times (5-15 min), molar ratio [stoich. ration (1.0:2.0), 1.25:2.0, 1.5:2.0, 2.5:2: 0, 3.0:2.0, 3.5:2.0,4.0:2.0, 5.0:2.0] and also crystallization time (2-6 hour) on the BMB yield (%) was investigated at 80 degrees C reaction temperature. It is found that, BMB precipitation synthesis with 90 % yield can be performed from 0.50 molar ration (BDH: Ba), under 80 degrees C, 15 minute, and 6 hours crystallization time. The structural properties of BMB powders were characterized by using XRD, FTIR and DTA-TG instrumental analysis technique.
Keywords: Barium metaborate; borax solution; precipitation; optimum parameters; CRYSTAL-GROWTH; BETA-BAB2O4; Materials Science; Physics